Supporting Gender and Sustainable Energy Initiatives in Central America, Volume 2 - Winrock International (World Bank, Washington, DC, 2014)
This report presents findings on the ESMAP-funded Central America Gender and Sustainable Energy project. The project has provided support to the Mesoamerican Gender in Sustainable Energy (GENES) Network, which seeks to enable the equitable access of women and men to sustainable energy services. Between April and July, 2002, a series of two bi-national and one tri-national workshop on gender and sustainable energy was conducted for members of GENES. Specific objectives were : become familiar with various types of renewable energy technologies, their applications and trends in their use; understand the principle concepts of gender equity; reflect on the relationship between gender equity, sustainable development, and renewable energy, and identify how key concepts of gender equity can be applied in the workplace and in the field; familiarize with recent advances in the gender and energy nexus; become familiar with gender methodologies, their uses and limitations. To ground the concepts presented, each workshop incorporated a technology demonstration and / or a field visit to a project site where participants could see one or more applications of sustainable energy technologies. These trips included exchanges on solar coffee drying and solar cooking; solar lighting and water pumping and brief field visits to projects involving photovoltaic pumping and electrification; solar fruit and wood drying; and the use of improved cook stoves.